If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=(5+x)3
We move all terms to the left:
6-((5+x)3)=0
We add all the numbers together, and all the variables
-((x+5)3)+6=0
We calculate terms in parentheses: -((x+5)3), so:We get rid of parentheses
(x+5)3
We multiply parentheses
3x+15
Back to the equation:
-(3x+15)
-3x-15+6=0
We add all the numbers together, and all the variables
-3x-9=0
We move all terms containing x to the left, all other terms to the right
-3x=9
x=9/-3
x=-3
| 23.5(6+4q)=60 | | 2x−5(x−1)=50. | | -3+2/3(6m-42)=-51 | | 53=8+10/x | | 0.58n=7.45 | | k=89.2=-47.62 | | -x/2=-52 | | 2-(5*x)=8 | | k=89.2=-47.2 | | 8(x+3)-2×=0 | | 2=9x+2 | | Y+2=-1/2(x-3) | | 2/6=16/b | | Y+2=-1/2(x,3) | | 1/5x+15=20 | | 2x+3=4x=5x-8 | | 49=x=12 | | 56x+139=180 | | 27x+90=180 | | n+6.5=13.5 | | 54x+113=180 | | 3/5(4x+1)=-19 | | 6x^2+30x=84 | | 17;y=163 | | 34-n=58 | | 8;b=56 | | 1.2+3.3(2.4-x)=41 | | 0.4x+3=0.8x-3 | | 4x-2(-2)=-9+5x-8 | | 3v-9v=48 | | -3|2x+1|=21 | | 2(x-15)=18x |